A Physician's Guide to Pain and Symptom Management in Cancer Patients - Abrahm, J. (Janet); O'Donnell, Arden; Moment, Amanda (Book collections on Project MUSE., 2014)
Now in its third edition, this comprehensive guide to managing pain and other symptoms for people with cancer has helped tens of thousands of patients and families.